The improving speaking skills through role playing strategies in students at muhammadiyah university of palangkaraya - Khunaifi, A R; Supriyadi, A (KnE Social Sciences, 2023)
There are four basic skills in English, namely Listening, Speaking, Reading and Writing, speaking skills are still not maximally spared by students. [1]which states that speaking is an event of conveying one’s intentions (ideas, thoughts, heart contents) to others using spoken language so that the meaning is understood by others. Not a few students of Universitas Muhammadiyah Palangkaraya still cannot understand well and do not understand the sentences spoken by the interlocutors who use English. Role playing is one of the strategies recently seen as very useful and effective in learning speaking because role playing can arouse enthusiasm and motivate students and provide an injection to speak in English. This study aims to determine student activities during training and to find out whether the use of role playing strategies can improve students’ speaking skills. This Classroom Action Research was designed and implemented in the Study Program at the Faculty of Agriculture and Forestry, Farmacy and the Islamic Faculty of Universitas Muhammadiyah Palangkaraya. The research subjects were 30 students of the Universitas Muhammadiyah Palangkaraya S1 Program. who take English courses. The stages of this research consisted of planning, implementing the action, observing and reflecting. The results obtained from this activity based on the reflection stage were that the average score of students was 7.5 on the speaking ability test where in the initial test the average student score was below 70. Student activities in role playing activities also increased where they could speak using English with a predetermined theme although there are still some vocabulary and grammar that need to be improved. Keywords: Speaking skills; role playing; basic skills; English